Risk of Malignancy and Tuberculosis of Biological and Targeted Drug in Patients With Spondyloarthritis: Systematic Review and Meta-analysis of Randomized Controlled Trials - Man, Siliang; Hu, Lidong; Ji, Xiaojian; Wang, Yiwen; Ma, Yingpei; Wang, Lei; Zhu, Jian; Huang, Feng (Frontiers in Pharmacology, 2021)
Objective Concerns exist regarding the potential development of malignancy and tuberculosis in patients with spondyloarthritis (SpA) treated with biologics. We assessed the extent to which biologic therapy may increase the risk of malignancy and tuberculosis in patients with SpA by meta-analysis to derive estimates of sparse harmful events occurring in randomized clinical trials (RCTs). Methods A systematic literature search was conducted in PubMed, EMbase, Web of Science, the Cochrane Library, and China Biology Medicine disc for RCTs evaluating the risk of sparse harmful events of biologic therapy in patients with SpA from inception through August 9, 2021. We calculated a pooled Peto OR for malignancy and tuberculosis in biologics-treated patients vs. placebo patients. The risk of bias on the included RCTs was assessed by using Cochrane Risk of Bias tool. Results In total, 63 studies were included in this meta-analysis, and 83 patients and 7 patients developed malignancy and tuberculosis, respectively. Overall, the risk of malignancy and tuberculosis was increased in SpA patients treated with biologics compared to placebo (malignancy: Peto OR: 2.49, 95%CI: 1.61-3.87, P<0.001; tuberculosis: Peto OR: 5.98, 95%CI: 1.29-27.76, P=0.022). Remarkably, compared to placebo, there was higher risk of malignancy for IL-17 inhibitors (Peto OR: 3.68, 95%CI: 1.20-11.30, P=0.023) and small molecule targeted drugs (Peto OR: 3.08, 95%CI: 1.37-6.90, P=0.043) in peripheral SpA, and for TNF receptor-Fc fusion protein in axial SpA (Peto OR: 7.18, 95%CI: 1.21-42.69, P=0.030). Besides, the risk of tuberculosis was higher for anti-TNFα antibody in axial SpA (Peto OR: 6.17, 95%CI: 1.03-37.13, P=0.046). Conclusions This meta-analysis showed an elevated risk of malignancy in patients with peripheral SpA treated with biologics, especially for IL-17 inhibitors, and small molecule targeted drugs, a slightly increased risk of malignancy in TNF receptor-Fc fusion protein in axial SpA, and increased risk of tuberculosis in patients with axial SpA treated with anti-TNFα antibody. These findings need to be validated by studies with larger population and longer follow-up.